Learners’ Perspectives on the Effectiveness of Writing and Reciting Poetry on their Language Skills and Motivation (Damascus University Journal of arts and humanities sciences, 2024)
The relationship between language and literature has always been inseparable. Research in language learning and pedagogy examines the impact that literature might have in the process of language learning, acquisition and development. Any form of literature could be used for the sake of developing different set of linguistic skills whether they are productive or receptive. In 2014, a poetry workshop has been launched in the English Department at Damascus University where students have to be exposed to the process of both writing and reciting poetry. This paper investigates the linguistic impact that the aforementioned workshop had on some of the participants. The research tools that were used are a questionnaire for 30 participants out of 43 who volunteered to take the questionnaire; the results of which were analyzed using SPSS, alongside a semi-structured interview with one of the workshop’s supervisors and the observation of the researcher. The results suggest that the process of writing and reciting poetry positively contributed in boosting learners’ motivation to learn English, boosted their confidence, and positively influenced both their receptive and productive skills alongside with their grammar and vocabulary.
Keywords: Perspectives